Adobe After Effects CS4 studio techniques - Christiansen, Mark (Visual effects specialist) (Peachpit Press, 2009)
This is the only book in the After Effects market to focus exclusively on the creation of visual effects, and is a one-stop resource for anyone who wants in-depth explanations that demystify the realm of visual effects and how they were created, thanks to veteran author Mark Christiansen's friendly and accessible style. A thoroughly packed, informative read, this masterful guide focuses on explaining the essential concepts, features, and techniques that are key to creating seamless movie-quality visual effects. Users who are comfortable with After Effects will find a helpful review of After Effects fundamentals--managing footage, viewing and editing layers, animating type, and more--so they can learn how to work smarter and more efficiently. Readers of all levels will learn core techniques for effects compositing including color matching, keying, rotoscoping, motion tracking, emulating the camera, and concluding with using expressions in After Effects, written by contributor and expert Dan Ebberts. The final section of the book delves into creative explorations, demonstrating professional effects that readers might want to re-create. Readers will also find comprehensive coverage of all that's new and makes this version of Adobe's effects program such a boon to video pros of all stripes: searchable timelines and projects, Photoshop 3D layers import, the Cartoon effect, Imagineer Systems' Mocha for Adobe After Effects, improved workflow for mobile devices, and more. Throughout the book, beautiful full-color examples demonstrate what's possible, while the companion DVD offers demos of After Effects CS4, sample footage, and software plug-ins.